Implementasi Manajemen Mutu di SDN Prambon - Indraswati, Dyah; Sutisna, Deni (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2020)
The purpose of this research is to describe how the implementation of school management to improve the quality of education at SDN Prambon, Dagangan, Madiun. This study uses a qualitative descriptive approach. Data collection techniques are conducted with interviews, observations, and documentation. Indicators developed by researchers as guidelines for data retrieval include school planning, school program implementation, school leadership, and monitoring and evaluation. Data analysis techniques include data reduction, data presentation, and withdrawal of conclusions. The validity test of the data is done by technique triangulation and source triangulation. The education process in Prambon SDN has fulfilled the quality education criteria which includes: 1) The effectiveness of the principal's leadership; 2) active participation of all interested components in the school; 3) The effectiveness of the teaching-learning process; 4) relevant curriculum; 5) Directed vision, mission, and objectives; 6) Conducive school climate and environment; 6) Community involvement and learners parents. The research implication is that the leadership and managerial abilities of principals are imperative to realize effective school management. The quality of education at SDN Prambon has the opportunity to be dynamically and innovatively revised so as to achieve ever increasing quality standards. Improving the quality of education must be carried out continuously and involve all components in schools.